Exploring Feeding Difficulties in Children : the Generosity of Acceptance: Volume 1. - Desmarais, Jane (Karnac Books, 2003)
Volume I of an edited collection that examines feeding difficulties and eating disorders in children and adolescents. Volume I concentrates on feeding difficulties in children from as young as five months. It consists of clinical cases that describe the process of psychoanalytic psychotherapy used to treat the patients. The contributors look at the underlying causes for the disorders and the profound effects on the patients and their families and friends.